Environmental strategy and sustainability - Heikkurinen, Pasi (Springer, 2011)
This chapter describes two alternative approaches to environmental strategy, namely instrumental strategy and awareness strategy. In order to have a successful environmental strategy values, actions and words must be aligned, and therefore it is vital that managers, leaders and academics identify the strategy approach at issue. Values based on utilitarian ethics; passive/reactive/proactive actions; and pragmatic/image-driven discourses all characterize an instrumental strategy. Values based on virtue/duty ethics; entrepreneurial/creative actions; and reflective/identity-driven discourses all characterize an awareness strategy. In the instrumental strategy the environmental responsibility is mainly a tool to achieve economic gains, whereas in the awareness strategy the environmental responsibility is a tool to achieve environmental gains. As both of these approaches can be classified under corporate environmental responsibility the strategies can be seen to contribute to environmental sustainability. However, the awareness strategy maximises to contribution to sustainability.
Keywords: Ma; ympäristäarvot; ympäristöjohtaminen; ympäristäetiikka; kestävä kehitys; environmental policies; environmental protection; environmental management; value theory; ethics; sustainability; yhteiskuntavastuu